Financial Analysis of Eucheuma cottoni in Bontang Kuala Village, Bontang City - Fitriyana, Fitriyana; Helminuddin, Helminuddin; Ningsih, Etik Sulistiowati (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
Research analysis of the Eucheuma cottoni seaweed cultivation business was conducted in July-September 2022 located in Bontang Kuala Village, Bontang City. The purpose of this study was to analyze the E.cottoni seaweed cultivation business financially by calculating production costs, revenue, and profits from the E.cottoni seaweed cultivation business, and analyzing the feasibility of E.cottoni seaweed cultivation business in Bontang Kuala Village, Bontang City. The selection of the location of this research was carried out intentionally with the consideration that there were E.cottoni seaweed cultivation business actors in Bontang Kuala Village, Bontang City, and the determination of respondents was carried out by census. Date using analysis with the formula Total cost (TC), Revenue or gross income (TR), profit analysis (π), Financial analysis Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback period. The results showed that the investment value incurred by E.cottoni seaweed cultivators was 77,726,000 with the largest investment cost being the drying floor of IDR 30,000,000 and the smallest investment cost being a knife of IDR 24,000. The revenue obtained by E.cottoni seaweed cultivators was 345,600,000/year with the selling price of dried seaweed at the time of this research carried out at IDR 8,000/kg of the amount of dried seaweed production of 34,560 kg/year. NPV obtained from the calculation of 429,564,890. Net B/C generated in the seaweed cultivation business in Bontang Kuala Village is 6.53. The IRR value obtained is 137%. The payback period (PP) value obtained based on calculations is 1.5 years or 18 months. Based on the calculation obtained NPV>0, Net B / C>1, IRR>OCC (3%) seaweed cultivation in its business in Bontang Kuala Village the development of its business is feasible and can be continued because it can still cover the operational costs incurred and make a profit.